2021
DOI: 10.1177/17585732211064815
|View full text |Cite
|
Sign up to set email alerts
|

Large segmental defects in midshaft clavicle nonunion treated with autologous tricortical iliac crest bone graft

Abstract: Background To evaluate the use of intercalary iliac crest bone graft in the treatment of clavicle nonunion with a large segmental bone defect (3–6 cm). Methods This retrospective study evaluated patients with large segmental bone defects (3–6 cm) after clavicle nonunion, treated with open reposition internal fixation and iliac crest bone graft between February 2003 and March 2021. At follow-up the Disabilities of the Arm, Shoulder and Hand (DASH) questionnaire was administered. A literature search was performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
(41 reference statements)
0
3
0
Order By: Relevance
“…Several studies have focused on the reconstruction of segmental osseous defects using ICBG or FVFG after non-union of the clavicle [11,[33][34][35][36][37][38][39][40]. Most of these were case reports or case series [33][34][35][36][37][38][39][40] and only one of the studies had FRI as their main focus area [11].…”
Section: Treatment Strategiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have focused on the reconstruction of segmental osseous defects using ICBG or FVFG after non-union of the clavicle [11,[33][34][35][36][37][38][39][40]. Most of these were case reports or case series [33][34][35][36][37][38][39][40] and only one of the studies had FRI as their main focus area [11].…”
Section: Treatment Strategiesmentioning
confidence: 99%
“…Several studies have focused on the reconstruction of segmental osseous defects using ICBG or FVFG after non-union of the clavicle [11,[33][34][35][36][37][38][39][40]. Most of these were case reports or case series [33][34][35][36][37][38][39][40] and only one of the studies had FRI as their main focus area [11]. The use of ICBG showed a good outcome with union rates ranging from 75% to 100%, with a significant improvement in shoulder function and pain reduction after surgery [35][36][37][38][39].…”
Section: Treatment Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when initial attempts at treatment of nonunion fail and are associated with significant bone loss, there is much less literature available [7][8][9]. A single recent study was identified that focused on tricortical iliac crest grafts for clavicle fracture nonunion, with a sample size of only five cases, that demonstrated the successful use of tricortical iliac crest grafts in large clavicle nonunion defects rather than vascularized grafts from other locations [10]. To add to this very small dataset, we present two cases of clavicle fractures that failed both initial osteosynthesis and an attempted revision procedure.…”
Section: Introductionmentioning
confidence: 99%